Strategy for Improving Ship Security Systems and Port Facilities with Implementation International Ship and Security (ISPS) Code in Branta Area - Iqnatia Adinda; Romanda Annas Amrullah; Eka Nurmala Sari Agustina; Rizqi Aini Rakhman (Pusat Riset dan Inovasi Nasional, 2024)
International Ship and Port Security (ISPS) Code or the International Code for Security of Ships and Port Facilities is an international regulation that complements the 1974 SOLAS Convention. Security of Ships and Port Facilities refers to port facilities and consists of Part A as orders and Part B as recommendations, which are stipulated in all ports in Indonesia, the Branta Area, one of them. ISPS Code created to facilitate shipping activities, both in terms of ship security and port facilities. The aim of this research is to describe strategies for improving ship security systems and port facilities through implementation ISPS Code in the Branta Area. The data collection technique in the research was carried out by interviews and then analyzed using SWOT. This research methodology uses mix method by collecting data directly in the field. This type of research is quantitative research analyzed using the SWOT method. The research was conducted within 12 months with. The population is ships entering and exiting the Branta area and also users of the sample port facilities Purposive Sampling. The research carried out this by distributing questionnaires that had been validated by experts. The results of the research can be obtained that the matrix value of the internal factors is 3.43 and the matrix value of the external factors is 3.44, the Cartesian diagram is in quadrant I, namely strategy aggressive .